WORK STRAIN, ABSENCE, AND INTENTION OF QUITTING JOB - FROM A PERSPECTIVE OF OCCUPATIONAL DIFFERENCE - Kirk S. Chang; Teddy Oswari (Jurnal Psikologi, 2008)
This research investigated how occupations influenced on stress and behaviors at work using questionnaire surveys (N = 613). Four heterogeneous occupations were recruited, including: high school teachers, shop clerks, factory employees and civil servants. Civil servants reported more sources of pressures, shop clerks reported higher levels of work strain, factory employees reported lower occurrence of absence behavior, and high school teachers reported lower intention of quitting job and higher working morale. The differences in stress and work behaviors across four occupations were due to two major factors. First, occupational differences, i.e., uniqueness and culture within the occupation. Second, individual demographics, i.e., marital status, education, job tenure, position rank and age. These individual demographics also offered account of differences in absence behavior, intention of quitting job and low working morale across four occupations. Implications of the findings and suggestion for future research are discussed.